Intestinal Flora Metabolite Trimethylamine Oxide Is Inextricably Linked to Coronary Heart Disease. Issue 3 (19th March 2023) - Zhang, Honghong; Jing, Lele; Zhai, Changlin; Xiang, Qiannan; Tian, Hongen; Hu, Huilin
Abstract: Atherosclerotic coronary heart disease is a common cardiovascular disease with high morbidity and mortality. In recent years, the incidence of coronary heart disease has gradually become younger, and biomarkers for predicting coronary heart disease have demonstrated valuable clinical prospects. Several studies have established an association between coronary heart disease and intestinal flora metabolites, including trimethylamine oxide (TMAO), which has attracted widespread attention from researchers. Investigations have also shown that plasma levels of TMAO and its precursors can predict cardiovascular risk in humans; however, TMAO's mechanism of action in causing coronary heart disease is not fully understood. This review examines TMAO's generation, the mechanism through which it causes coronary heart disease, and the approaches used to treat TMAO-caused coronary heart disease to possible avenues for future research on coronary heart disease and find new concepts for the treatment of the condition.